1998
DOI: 10.1071/r97075
|View full text |Cite
|
Sign up to set email alerts
|

Energy balance and ovulation: small cages versus natural habitats

Abstract: In the laboratory, ovulation is suppressed when a mammal is in negative energy balance whether that state is caused by inadequate food intake, excessive locomotor activity or heavy thermoregulatory costs. In this paper, knowledge generated in the laboratory about the link between ovulation and energy balance is examined in relation to the kinds of energetic challenges mammals actually face in natural habitats. When viewed in that context, several conclusions can be drawn. First, females ovulate whenever extant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
36
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 0 publications
2
36
1
2
Order By: Relevance
“…The paired female, however, showed elevated FPM concentrations on the last sampling day and we may have missed the luteal phase because faecal sampling was conducted only every second day. Body mass and age of a female are important factors governing the reproductive process (Bronson 1998). It is, however, unlikely that these affected our results.…”
Section: Discussioncontrasting
confidence: 48%
“…The paired female, however, showed elevated FPM concentrations on the last sampling day and we may have missed the luteal phase because faecal sampling was conducted only every second day. Body mass and age of a female are important factors governing the reproductive process (Bronson 1998). It is, however, unlikely that these affected our results.…”
Section: Discussioncontrasting
confidence: 48%
“…These animals also display ability to cancel, increase, or decrease reproductive effort at a later stage long after the initiation of reproduction per se. In this sense, capital breeding mammals may be similar to male asp vipers: individuals with more body reserves are more likely to reproduce, but do not require a threshold level of reserves to initiate reproduction (Bronson, 1998; this paper). Thus, they do not satisfy the "threshold" criterion for capital breeding (Stearns, 1992).…”
Section: Discussionmentioning
confidence: 97%
“…For example, several mammals are classified as typical capital breeders (Festa-Bianchet et al, 1998) but recent reviews on captive and natural populations of mammals found no support for the widely accepted "adaptationist argument that females should delay ovulation until they have sufficient energy reserves to support pregnancy and lactation" (Bronson, 1998;Schneider, Zhou, and Blum, 2000). These animals also display ability to cancel, increase, or decrease reproductive effort at a later stage long after the initiation of reproduction per se.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leptin has a reciprocal regulatory relation with ghrelin, a messenger coming directly from the gastrointestinal tract (Kalra et al 2005). Nutrition is hypothesized to be regulated by cholecystokinin, leptin and insulin, decreasing food intake and ghrelin, and increasing food intake (Bronson 1998). Cholecystokinin and ghrelin regulate food intake in the short term, whereas leptin and insulin regulate food intake over longer periods (Gorissen et al 2006).…”
Section: Discussionmentioning
confidence: 99%